A Novel 3D Osteoblast and Osteocyte Model Revealing Changes in Mineralization and Pro-osteoclastogenic Paracrine Signaling During Estrogen Deficiency - Naqvi, Syeda Masooma; Panadero Pérez, Juan Alberto; Kumar, Vatsal; Verbruggen, Anneke S. K.; McNamara, Laoise M. (Frontiers in Bioengineering and Biotechnology, 2020)
Recent in vitro studies have revealed that the mechanobiological responses of osteoblasts and osteocytes are fundamentally impaired during estrogen deficiency. However, these two dimensional (2D) cell culture studies do not account for in vivo biophysical cues. Thus, the objectives of this study are to (1) develop a three dimensional (3D) osteoblast and osteocyte model integrated into a bioreactor and (2) apply this model to investigate whether estrogen deficiency leads to changes in osteoblast to osteocyte transition, mechanosensation, mineralisation and paracrine signaling associated with bone resorption by osteoclasts. MC3T3-E1s were expanded in media supplemented with estrogen (17β-estradiol). These cells were encapsulated in gelatin-mtgase before culture in (1) continued estrogen (E) or (2) no further estrogen supplementation. Constructs were placed in gas permeable and water impermeable cell culture bags and maintained at 5% CO2 and 37ºC. These bags were either mechanically stimulated in a custom Hydrostatic Pressure (HP) bioreactor or maintained under static conditions (control). We report that osteocyte differentiation, characterized by the presence of dendrites and staining for osteocyte marker dentin matrix acidic phosphoprotein 1 (DMP1), was significantly greater under estrogen withdrawal compared to under continuous estrogen treatment (day 21). Mineralization (bone sialoprotein (BSP), osteopontin (OPN), alkaline phosphatase (ALP), calcium and gene expression associated with paracrine signaling for osteoclastogenesis (receptor activator of nuclear factor kappa-β ligand (RANKL)/ osteoprotegerin OPG ratio) were significantly increased in estrogen deficient and mechanically stimulated cells. Interestingly BSP and DMP-1 were also increased at day 1 and day 21 respectively, which play a role in regulation of biomineralization. Furthermore, the increase in pro-osteoclastogenic signaling may be explained by altered mechanoresponsiveness of osteoblasts or osteocytes during estrogen withdrawal. These findings highlight the impact of estrogen deficiency on bone cell function and provide a novel in vitro model to investigate the mechanisms underpinning changes in bone cells after estrogen deficiency.